Implementasi Kebijakan Penanganan Sampah di Kota Semarang berdasarkan Peraturan Daerah Kota Semarang Nomor 6 Tahun 2012 tentang Pengelolaan Sampah - Febryanti, Indira; Suryaningsih, Margaretha (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Waste Handling is one of ways that Semarang Local Government do to overcoming problem about the high amount of waste in Semarang City. Waste handling policy is important because waste is an important problem that need to be resolved to create a clean and health environment. This research will further elaborate the implementation of waste handling policy in Semarang City. The method that is used in this research is qualitative – descriptive type, with informants from the staff of Living Environment Agency of Semarang, Final Processing Place Jatibarang whose specially handling about waste handling policy in Semarang City, Society Group who doing waste management, and society in Semarang City. The purpose of this study is to analyze the implementation of waste handling using 5 accuracy theory from Riant Nugroho and describe factors that influence the policy implementation using theory from Van Meter and Van Horn. The result of the research shown that in the policy implementation which is undertaken, there are problems related to socialiszation of the policy which not touching all society yet; society’s response that is not support waste handling policy; and process of society’s acceptance toward the policy which is showing refusal for the policy. Constraint factors of the waste handling policy are resources and social condition from Semarang’s societies. Reccomendation which is given from this research are; the government have to be more active in socializing waste handling policy, improvement of the human resources and facilities which supporting the policy; and addition and activating of TPS 3R in Semarang City that along with companion toward TPS 3R’s caretaker.